Studies on Phytotoxicity of Herbicides and Herbicide Mixtures and its effect on Yield of Direct- Sown Rice (Oryza sativa L.) - Mahapatra, Ashirbachan; Saha, Sanjoy; Munda, Sushmita; Shukla, R. K. (International Journal of Bio-resource and Stress Management, 2017)
The present investigation was carried out at Institute ResearchFarmofICAR-NRRI, Cuttack (Odisha) during wet season of 2016 to study the phytotoxicity of a new herbicide molecule XR-848 Benzyl Ester along with its mixture with Cyhalofop Butyl in different doses and its effect on yield of direct-sown rice. The experiment was laid out in Randomized Block Design (RBD) with three replications and nine treatments viz. four herbicide mixtures(T1-XR-848 Benzyl Ester+Cyhalofop Butyl 12% EC (w/v) @ 120(20+100)g ha-1, T2-XR-848 Benzyl Ester+Cyhalofop Butyl 12% EC (w/v) @ 150(25+125)g ha-1, T3-XR-848 Benzyl Ester+Cyhalofop Butyl 12% EC (w/v) @ 180(30+150)g ha-1 andT4-XR-848 Benzyl Ester+Cyhalofop Butyl 12% EC (w/v) @ 360(60+300)g ha-1), three alone herbicides(T5-XR-848 Benzyl Ester 2.5% EC (w/v) @ 25g ha-1, T6-XR-848 Benzyl Ester 2.5% EC (w/v) @ 30g ha-1 andT7-Bispyribac-Na 10% SC @ 30g ha-1), one weed free (T8)and an untreated weedy check (T9).Under phytotoxicity analysis, visual observations (Phyotoxic score), chlorophyll content and SPAD meter readings at 10, 20 and 30 days after treatment (DAT) of herbicides were taken, in which the T4proved to be the most phytotoxic causing a reduction of 29.41% in grain yield which was at par with the untreated weedy check. Whereas T2 showed a minimal phyotoxicity at initial stage with a quick recovery within 30 DAT of herbicide and was proved to be the best herbicide mixture yielding at par with the weed free (T8).